2008
DOI: 10.1161/strokeaha.107.485938
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Nitroimidazole In Vivo Hypoxia Imaging in Ischemic Stroke

Abstract: Background and Purpose-Nitroimidazole imaging is a promising contender for noninvasive in vivo mapping of brain hypoxia after stroke. However, there is a dearth of knowledge about the behavior of these compounds in the various pathophysiologic situations encountered in ischemic stroke. In this article we report the findings from a systematic review of the literature on the use of the nitroimidazoles to map hypoxia after stroke. Summary of Review-We describe the characteristics of nitroimidazoles as imaging tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
79
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(86 citation statements)
references
References 72 publications
3
79
0
2
Order By: Relevance
“…The incorporation of hydrophobic NI groups renders the derived HA amphiphilic, enabling the formation of GRVs in the aqueous solution (37,38). Moreover, NI provides an hypoxiasensitive element, which is expected to be bioreduced under hypoxic conditions (24,27). The reduced product with amine groups is water-soluble, leading to disassembly of GRVs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The incorporation of hydrophobic NI groups renders the derived HA amphiphilic, enabling the formation of GRVs in the aqueous solution (37,38). Moreover, NI provides an hypoxiasensitive element, which is expected to be bioreduced under hypoxic conditions (24,27). The reduced product with amine groups is water-soluble, leading to disassembly of GRVs.…”
Section: Resultsmentioning
confidence: 99%
“…To achieve hypoxia-responsive transduction, 2-nitroimidazole (NI), a hydrophobic component that has often been applied in cancer imaging due to its high sensitivity to the hypoxic condition in tumor sites, was used (24,25). NI can be converted to hydrophilic 2-aminoimidazoles under a hypoxic environment via a single-electron reduction catalyzed by a series of nitroreductases coupled to bioreducing agents, such as NADPH, a plentiful coenzyme in tissues (24)(25)(26)(27). We conjugated amine-functionalized NI with HA (molecular mass of 300 kDa), which is well known to have excellent biocompatibility and biodegradability (28)(29)(30).…”
Section: Significancementioning
confidence: 99%
“…In one study that used positron emission tomography with 18 F-fluoromisonidazole, believed to map the hypoxic viable tissue but not the normally perfused or the already necrotic tissue, 55 increased likelihood of neurological deterioration occurred if a large proportion of the hypoxic tissue subsequently progressed to infarction. 56 However, concomitant perfusion studies were not reported, and to what degree the hypoxic tissue defined with 18 F-fluoromisonidazole represents only penumbra is still not clear.…”
Section: Hypoxiamentioning
confidence: 99%
“…Radiolabeled nitroimidazole derivatives are used for imaging hypoxic tissue because the nitroimidazole residue is reduced to reactive chemical species that can bind to intracellular components in the absence of sufficient oxygen [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%